Case Report: A case of COL1A1–PDGFB fusion uterine sarcoma at cervix and insights into the clinical management of rare uterine sarcoma - Lu, Linghui; Wang, Shunni; Shen, Haoran; Zhang, Feiran; Ma, Fenghua; Shi, Yue; Ning, Yan (Frontiers in Oncology, 2023)
COL1A1-PDGFB gene fusion uterine sarcoma was an especially rare malignant mesenchymal tumor that was previously classified as an undifferentiated uterine sarcoma due to the lack of specific features of differentiation. Till now, only five cases have been reported, and here we presented another case recently diagnosed of Chinese female came with vaginal bleeding. She presented with a cervical mass at the anterior lip of cervix invading the vagina and treated with laparoscopic total hysterectomy plus bilateral salpingoophorectomy (TH+BSO) and partial vaginal wall resection with the final pathology of COL1A1-PDGFB fusion uterine sarcoma. Our aim is to propose the importance of differential diagnosis of this rare tumor, and early precise diagnosis may benefit patients from the target therapy of imatinib. This article also served more clinical evidence of this disease and clinical awareness of this rare sarcoma was expected to be aroused to avoid misdiagnosis.